Thermoelectric power factor performance of silicon-germanium alloy doped with phosphorus prepared by spark plasma assisted transient liquid phase sintering. (15th January 2018) - Murugasami, R.; Vivekanandhan, P.; Kumaran, S.; Suresh Kumar, R.; John Tharakan, T.
Abstract: This work reports on the successful attempt towards the swift synthesis of Silicon-Germanium (SiGe) alloy doped with phosphorus through spark plasma assisted transient liquid phase sintering. This proposed synthesis of homogeneous SiGe alloy warrants the very shorter duration (17 min.) as opposed to the conventional liquid and solid state synthesis methods which require several hours. SiGe alloys portray the ultra-fine grain features with an excellent relative density > 97%. SiGe alloy with P2.0  at.% exhibits n-type semiconducting behavior with the superior thermoelectric power factor of 21.87 μW/cm-K 2 at 750 °C. SiGe alloy reveals the bench marked Vickers hardness of 848 ± 27 HV0.3 . Graphical abstract: Image 1